PROJECT APPROACH: FACILITATING ELEMENTARY SCHOOL STUDENTS IN READING - Dessy Dwi Dwi Yudha Santhi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Metaphors in a written discourse such as in letters using bahasa Indonesia can be derived from the metaphorical expressions used by the writers to the editors, showing conceptualization which is based on what they experience, feel, and think in their life.This paper aims at finding out the universality of the concepts shown by the metaphors and the users using the metaphors. Using nonparticipant observation with  note-taking  technique,  the data  are  collected  and  chosen  purposively.  With distributional, referential, reflective introspective, and abductive inferential methods, the data are analyzed. The results indicate that metaphors can be grouped into universal,  specific,  and  public  ones  due  to  the  universality,  specification  of the concepts  conveyed  in,  and  the  users  using  them.  This       implies  that  bahasa Indonesia  conveys  similar concepts  as other languages  in the world do which is caused   by  the   experiences   from   different   time   and   places   encountered   by Indonesians living in an agricultural country.